Examination of Fracture Mechanisms in two Al – Ti – V – Cr – (Si) High Entropy Alloys - Chaskis Spyridon (EDP Sciences, 2021)
This work focuses on the examination of two High Entropy Alloys (HEAs), the AlTiVCr and AlTiVCr–Si7.2, which have been observed to fail in a brittle manner directly after casting. Understanding the failure mechanics is a prerequisite for an alternative enhanced alloy design in order to prevent early failure without loading application. The specimens were produced using the Vacuum Arc Melting methodology in a protective argon atmosphere. The material was re–melted five times in combination with electromagnetic stirring in order to achieve a fully homogenized microstructure. Based on our findings, the failure occurred in the first 10 minutes after casting during slow cooling. Similarly, the same took place during thermal treatment after the third re–melting. The specimens were first prepared for optical (OM) and scanning electron microscopy (SEM) analysis. The material consists of a coarse dendritic microstructure as well as a retained BCC phase, which is the AlTiVCr phase. In the AlTiVCr – Si7.2 alloy a uniformly dispersed, angular intermetallic compound, namely the Ti5Si3, was identified, which increases the failure resistance of the material. Based on these findings the alloy will be redesigned.